Nasogastric Tube Placement as an Unusual Cause of Iatrogenic Hemopneumothorax in a Geriatric Patient: A Case Report and Current Literature Review - Busra Ozdemir Ciflik; Mehmet Cetin; Necati Solak; Furkan Sural; Koray Aydogdu (Haseki Tıp Bülteni)
Iatrogenic hemopneumothorax is the presence of air and hemorrhagic fluid in the pleural space. It is a complication of invasive procedures performed for diagnosis and treatment. A 75-year-old woman with a history of cerebrovascular disease and aspiration pneumonia underwent wire-guided nasogastric tube (NGT) on the first day of palliative care follow-up because of the risk of aspiration with oral feeding. Posterior-anterior chest radiography was performed after the procedure because the patient had chest pain and tachypnea. Posterior-anterior chest radiography showed that the NGT guidewire was in the right costophrenic sinus and was associated with pneumothorax. Iatrogenic hemopneumothorax may develop secondary to many invasive procedures, as well as secondary to NGT, which is a simple clinical procedure. We aim to present an unprecedented case in which a new-generation NGT with a guidewire caused a hemopneumothorax during insertion.